New Species of Anthurium section Calomystrium from Costa Rica and Panama - Ortiz, Orlando O.; Croat, Thomas B. (Phytotaxa, 2016)
Five new species of Anthurium section Calomystrium from Central America are described here: A. filamatamaense sp. nov. from Costa Rica and A. lasabanetaense sp. nov., A. roseonaviculare sp. nov., A. solanoi sp. nov. and A. suffusum sp nov. from Panama. The new Panamanian taxa increase the number of species in Anthurium section Calomystrium to forty-two, of which 35 are endemic to the country. In the case of Costa Rica, the number of species increases to nine, of which, three are endemic.